Why non-inferiority is more challenging than superiority?. (May 2017) - Sormani, Maria Pia
Demonstrating non-inferiority in clinical trials is usually more challenging than showing superiority. In multiple sclerosis (MS), non-inferiority trials are rarely designed since they would require prohibitive sample sizes. In this brief report, the reasons why non-inferiority trials are usually larger than superiority trials is explored.